AHLI WARIS PENGGANTI MENURUT HAZAIRIN - Iwanudin, Iwanudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Hazairin is one of the clergy indonesia living in the all 20 M, one of the results of his mind was on the heirs a substitute for.The concept of the heirs replacement is a ijtihad done by hazairin in order to give solutions from trouble those who are most are the heirs but terhijab by brother the heir and they lived in a state of poor and concern, in addition they did not receive attention from the of heirs get inheritance .Who when in khazanah thought islamic kewarisan so far, unknown with the term heirs a substitute for as thought hazairin, islamic offers in this is to solve the problems in over can be settled by system will wajibah.Will wajibah had the foundation time which strong in to solve problems in top and does not overlook enforcement justice. In writing are presented concepts heirs a substitute for according to Hazairin which then writer hold analysis by means of land those opinions of other scholars about discussion is .And can writer concluded that: (1) According to Hazairin in terms of dad died worthy of to grandpa, so grandson ( male or female ) can replace position heirs, which in itself called the heirs a substitute for. (2) Approach in use hazairin in an effort to formulate islamic law is the approach sosio-kultural-historis which is certainly with continued reference to postulates of nash . This based that islamic law / fiqh can change according to the situation and the condition of being step around him. (3) New position as an heir, of heirs that is substituted who had died the world first is domain ijtihadiyah that may be the dissent. (4) the system will wajibah more acceptable than the heirs a substitute for directly , here the concept of the heirs a substitute for apply in the process will wajibah , because will wajibah have rooted in khazanah thought kewarisan islam and ultimately achieve justice. (5) to achieve kemashlahatan, in which reflect justice and legal certainty, for the muslim community indonesia should hold on to ijma ’ ulama indonesia espoused in article 185 compilation islamic law .